2018
DOI: 10.21873/anticanres.12977
|View full text |Cite
|
Sign up to set email alerts
|

Dclk1 Inhibition Cancels 5-FU-induced Cell-cycle Arrest and Decreases Cell Survival in Colorectal Cancer

Abstract: is frequently used in colorectal cancer treatment, but with limited success. The aim of the present study was to explore the cytotoxic effects of 5-FU, in combination with inhibition of doublecortin-like kinase 1 (Dclk1), a tumor stem cell marker that regulates pro-survival signaling in colorectal cancer cells, in the human colon cancer cell line, The effects of 5-FU treatment plus Dclk1 inhibition on the phosphorylation of checkpoint kinase 1 (Chk1), cell cycle, DNA damage, apoptosis, and cell survival in CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 6 publications
2
23
0
Order By: Relevance
“…To evaluate the in vivo anticancer of dioscin, SMMC7721 and HepG2 cells tumour xenograft model were used and 5‐FU, which is a fluorinated pyrimidine analogue that acts as an antimetabolic agent, inhibiting thymidylate synthase and interfering with RNA synthesis and representing the standard first‐line chemotherapy to treat cancer (Suehiro et al, ), was applied as the positive drug. As shown in Figure a, the significant differences in tumour volumes were found based on tumour images after 27 days of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the in vivo anticancer of dioscin, SMMC7721 and HepG2 cells tumour xenograft model were used and 5‐FU, which is a fluorinated pyrimidine analogue that acts as an antimetabolic agent, inhibiting thymidylate synthase and interfering with RNA synthesis and representing the standard first‐line chemotherapy to treat cancer (Suehiro et al, ), was applied as the positive drug. As shown in Figure a, the significant differences in tumour volumes were found based on tumour images after 27 days of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…To further comprehend the biological effects of the DEGs identified and the pathways associated with CRC that they accumulate in, GO term and KEGG pathway enrichment analyses were performed. The results of the GO term functional analysis indicated that the DEGs identified were mainly involved in the following terms: 'Mitotic nuclear division', 'positive regulation of cell proliferation', 'one-carbon metabolic process', 'cell division', 'immune response', 'hormone (26)(27)(28). However, the underlying mechanisms through which the corresponding proteins in these signalling cascades promote tumorigenesis remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…For example, phosphoproteomics identified new connections between tumor suppressor loss and signaling, including upregulation of RIPK3 in MAP3K1 mutant tumors, the WNT pathway mediator TNIK1 in ARID1A mutant tumors, and the microtubule-associated kinase and neuroendocrine differentiation markers MAST4 and DCLK1 (Liu et al, 2016) in GATA3 mutant tumors. The first two findings suggest potential therapeutic directions in the difficult arena of targeting tumor suppressor loss, whereas DCLK1 inhibition via the small-molecule kinase inhibitor LRRK2-IN-1 has shown preclinical efficacy in some cancers (Kawamura et al, 2017;Suehiro et al, 2018;Weygant et al, 2014). Proteomics and acetylproteomics profiling in the context of metabolism also revealed, for the first time in a large BRCA cohort, marked differences in metabolic enzyme expression and acetylation between luminally-and basally-enriched subtypes, which may translate to a better understanding of metabolic vulnerabilities.…”
Section: Ll Open Accessmentioning
confidence: 99%